Análisis organizacional del camal municipal y su incidencia en la calidad del producto; caso estudio, Camal Municipal del cantón Montalvo, provincia de los ríos, año 2014 - Robayo Gonzalez, Braulio Alonso (2015)
The Municipal Slaughterhouse Canton Montalvo is a company dedicated to providing an excellent level of quality in the provision of services in our county users.This research study organizational analysis and its impact on product quality local municipal slaughterhouse case study Montalvo Canton, having the commitment to meet or exceed the expectations of users, ensuring compliance with the specifications and adding value to services and provided administrative and organizational management to achieve individual and team participation of all administrative staff and service, a commitment to continuous improvement and speed of response to users who come to use their facilities. Through this study it was determined continuously programming and implementing training for the administrative and operational staff of the municipal slaughterhouse Canton Montalvo with regard to customer service, administrative management in order to improve service to users and geared towards rated performance of its activities and processes. Noting that must issue an internal regulation that determines the procurement process works and based on specific measures in accordance with the general rules of public sector teams, managers must adapt the facilities of the municipal slaughterhouse with new technological equipment in terms to slaughter for user satisfaction and thus provide a quality service and efficiency. And finally design an organizational structure and building planning department that this articulated with the departments of the municipal slaughterhouse for the development, implementation and monitoring of the annual operating plan based on the policies, regulations and the procurement of works and equipment.